Konsep Supervisi Klinik dalam Pandangan Kajian Islam: Menjawab Tantangan dan Peluang Peningkatan Kualitas Pembelajaran - Firmansyah, Ahmad; Sudadi , Sudadi; Offorma, Grace C; Okpala, Helen N (Edukais : Jurnal Pemikiran Keislaman, 2025)
This study analyzes the application of clinical supervision in an effort to improve the quality of teaching at SD Negeri 002 Kuaro. Clinical supervision is applied as a collaborative approach to help teachers identify and improve weaknesses in learning through planning, observation, and feedback stages. A descriptive method with a qualitative approach is used in this study, which involves direct observation, structured interviews, and documentation. The results of the study show that clinical supervision carried out in a structured and scheduled manner has a positive impact on improving teachers’ professional competence. The teachers succeeded in improving classroom mastery, developing appropriate Learning Implementation Plans (RPP), using effective teaching strategies, and preparing learning evaluations more optimally. However, the study also found challenges such as time constraints, variations in teacher competencies, and resistance to change. This study concludes that clinical supervision is an effective strategy in supporting the improvement of teaching quality, provided that it is supported by careful planning, adequate training, and ongoing institutional support